Fatores de risco para o parto prematuro em puérperas com parto pré-termo atendidas na Fundação Santa Casa de Misericórdia do Pará - SOUZA, Lana Fabíola Silva e (2023)
Despite the advances in perinatolgy in recent years, prematurity remains the leading cause of neonatal morbidity and mortality, representing one of the biggest challenges for the current obstetrics. Among the causes of perinatal mortality, 61.4% are associated with prematurity. Several factors are associated with preterm childbirth. The aim of this study s to assess which risk factors preterm delivery in pregnant women in Fundação Santa Casa de Misericórdia do Pará, a referral hospital for maternal and child in Belém. Were investigated 100 postpartum women who had preterm delivery wards of the hospital Fundação Santa Casa de Misericórdia do Pará, being subjected to an interview about the socioeconomic characteristics, personal history, gynecological history, obstetric history and current pregnancy. The association between the studied factors and preterm birth were analyzed and described. Gaining importance with low education, low socioeconomic status, have chronic diseases, poor prenatal care, first pregnancy, anemia, urinary tract infection, bacterial vaginosis and premature rupture of membranes.